GAGASAN PENAMBAHAN SANKSI PIDANA TERHADAP GURU PELAKU KEKERASAN SEKSUAL ANAK DIDIK DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Wyndaria, Annisa; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
As if it never stops, the number of cases of sexual violence which is always increasing every year, especially sexual violence against minors committed by teachers against their students. It is time to carry out a reform of criminal law because the existing law has not provided a deterrent effect and prevention of criminal acts of sexual violence in Indonesia.This type of research is classified as normative legal research. The data source is secondary data which is divided into 3 (three), namely primary, secondary and tertiary legal materials. literature review. In this case, a researcher must be observant and precise to find data contained both in regulations and literature that have a relationship with the problem under study. In drawing conclusions using a deductive thinking method that draws conclusions from a general statement into a statement or a special case.From the results of the study, the first is about the application of criminal sanctions against teachers of perpetrators of child sexual violence in court decisions. There are several changes in the Law due to the prevalence of sexual violence crime in Indonesia. Law Number 23 of 2002 was amended to Law Number 35 of 2014 then underwent another change with the issuance of Law Number 17 of 2016. However, of the three regulations in their implementation, they have not been able to create a deterrent and preventive effect on teachers of sexual violence perpetrators. against students in Indonesia and castration cannot be implemented because it violates the medical code of ethics. Second, ideally, criminal sanctions for teachers who commit sexual violence against students in the reform of criminal law in Indonesia, namely the idea of an additional criminal sanction for revoking certain rights in the form of revocation of professional rights or positions against teachers who commit sexual violence against students in Indonesia so that it can have an effect. deterring the perpetrators and as a deterrent for teachers who want to commit the same crime so that the community, especially parents and children, can feel safe and at ease.Keywords: Ideas-Crime-Teacher-Sexual Violence-Students